Lights and Shadows of Paracentesis: Is an Ultrasound Guided Approach Enough to Prevent Bleeding Complications? - Marta Patturelli; Luca Pignata; Pietro Venetucci; Maria Guarino (Livers, 2023)
Paracentesis is a validated procedure for diagnosing and managing ascites. Although paracentesis is a safe procedure with a 1–2% risk of complications such as bleeding, it is necessary to inform the patient about the possible adverse events. We would like to share our experience with two cases of bleeding after paracentesis. In our unit, two major hemorrhagic complications occurred in 162 procedures performed over the year 2020 (frequency of bleeding complications: 1.2%). We report two clinical cases of post-paracentesis abdominal wall hematomas. Despite a similar clinical presentation, the management approach was different: in the first case, embolization of the epigastric artery supplying the hematoma was performed. In the second case, conservative treatment was adopted. Our report aims to provide food for thought about a potentially challenging hemorrhagic complication, even with the risk of adverse outcomes.